2017
DOI: 10.1093/ageing/afx008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic conditions and use of health care service among German centenarians

Abstract: the higher prevalence of dementia and rheumatic disease/arthritis in long-term care compared to other care settings emphasises the role of these diseases in relation to the loss of physical and cognitive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
13
17
0
Order By: Relevance
“…Multimorbidity as predictor of LTC admission [13] seems to hold in the oldest old women, as our results suggest. Consonant with previous studies [9,13,26,27], our results also show that LTC admissions are more common in women than men whereas mortality is higher in men in this age group. This might be one reason why we did not find associations between chronic conditions or multimorbidity and LTC admission in men.…”
Section: Discussionsupporting
confidence: 90%
“…Multimorbidity as predictor of LTC admission [13] seems to hold in the oldest old women, as our results suggest. Consonant with previous studies [9,13,26,27], our results also show that LTC admissions are more common in women than men whereas mortality is higher in men in this age group. This might be one reason why we did not find associations between chronic conditions or multimorbidity and LTC admission in men.…”
Section: Discussionsupporting
confidence: 90%
“…Apart from in Switzerland, the share of institutionalised centenarians in our sample agreed with the findings of several studies (from 42.1% in Portugal to 53.7% in Canada) 9 10 13 14. However, other works disclosed proportions above 60%, and a study based on European census data revealed considerable geographical variations, with percentages ranging from 10% to 90% 6 15 16.…”
Section: Discussionsupporting
confidence: 91%
“…The number of medical visits seemed to match differences in the number of general practitioners in each country, but the relationship was less noticeable when taking all practising physicians together. In other studies addressing the topic, >95% of centenarians had seen a doctor during the previous 12 months 9 10 15. Regarding nursing care at home, its more frequent use in Switzerland and Sweden was comparable to that reported in Germany (52.8%) and Canada (55.9%), whereas its use in France and Denmark was closer to that recently found in Portugal (44.4%) 9 10 13.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations